Teacher Engagement Scale for Professional Development - Cara L. Kelly,; Laura L. Brock,; Julie Dingle Swanson,; Lara Walker Russell, (Journal of Educational Issues, 2024)
Teacher professional development aims to bolster effective instructional practices that enhance student learning. The development of the Sustained Investment and Teacher Engagement Scale for Professional Development (SITES-PD) grew out of a need to understand how teachers respond to opportunities for professional learning in ways that contribute to skill improvement. One hundred and eight elementary teachers participated in a sustained professional development coaching intervention. Prior to and following the intervention, data were collected from multiple sources (e.g., teacher report, blind classroom observations). For the development of this instrument, coaches rated teacher engagement with opportunities for professional learning. Exploratory factor analysis reveals a one factor solution and that a summed composite of eight items is appropriate. Reliability and validity results suggest the SITES-PD instrument may be a useful tool for investigating the underlying mechanisms that mediate the efficacy of teacher professional development interventions.